Convective parameterization in mesoscale models - Weissbluth, Michael J., author (Colorado State University. Libraries, 1991)
Currently, there is no adequate cumulus parameterization that is suitable for use in mesoscale models having horizontal resolutions between five and fifty kilometers. Based on the similarity of the temporal and spatial evolution of the vertical variances between a CC OPE supercell and a generic tropical squall line as explicitly simulated by the Colorado State University Regional Atmospheric Modeling System (CSU RAMS), a modified second order closure scheme has been developed which allows the prediction of deep convective fluxes. The Mellor and Yamada 2.5 level closure has been modified to predict solely on w w' using Zeman and Lumley's formulation of the buoyancy-driven mixed layer to close the pressure terms and the eddy-transport term. The extension to the free atmosphere has been accomplished by representing the deep cumulus fluxes as proportional to the difference between a cloud model derived property and the environmental value. This cloud model has been calibrated and generalized by comparisons with conditionally sampled data from the two explicitly simulated storms. The deep cumulus tendencies of heat, moisture and hydrometeors are specified by a mesoscale compensation term and a convective adjustment term. As above, the convective adjustment term is specified as the difference between a cloud model derived property and its environmental value, but is modulated by a time scale determined by an integrated value of w'w'. The mesoscale compensation term is a product of the vertical gradient of the appropriate scalar and a constant determined through a moist static energy balance. One unique feature of this approach is that the parameterization is not simply a local grid column scheme; w'w' is transported by the turbulence as well as the mean horizontal and vertical winds. Thus, the scheme responds to shear and is more global in nature than current cumulus parameterizations. Furthermore, the scheme provides explicit cumulus source functions for all hydrometeor species. Results of an explicit simulation of two dimensional sea-breeze convection over the Florida peninsula will be compared to simulations on coarser grids using the generalized cumulus parameterization.
October 28, 1991.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1991.
Keywords: Convective clouds -- Mathematical models; Convection (Meteorology); Cumulus; Mesometeorology